Migraine in the emergency department: A retrospective evaluation of the characteristics of attendances in a major city hospital in the United Kingdom. (20th May 2022) - Logan, A-M; Reid, I; Yogarajah, M; Wang, C; Greenwood, N; Edwards, M; Jarman, H; Nirmalananthan, N
Introduction: Detailed Emergency Department attendance data for migraine are needed for service redesign. Methods: A service evaluation was undertaken, classifying adult emergency department headache attendances using the International Classification of Headache Disorders migraine C-E criteria, evaluating attendance characteristics. Results: Migraine/Probable migraine diagnosis was documented in 58% but coded in 24% attendances by ED clinicians. 29% of patients used no analgesia before attending, 43% attended ≥4 days after onset and 19% arrived by ambulance. Conclusion: This evaluation highlights sub-optimal acute management and discrepancy between migraine coding and diagnosis contributing to underreporting. We recommend further evaluation of identified cohorts and headache proforma use.